К вопросу о связи кровососущих двукрылых насекомых с некоторыми прокормителями в условиях Степи УССР - Шевченко, А.К.; Грицай, В.Ф.; Балабанова, Р.А. (Вестник зоологии, 1973)
The data are presented on trophic connections of complex of blood-sucking Diptera (mosquito, flies and biting midges) in two biotopes of the steppe zone of the Ukraine (Donetsk suburbs and Veliko-Anadolskian forest). It was found out that some species attack the investigated providers (man, cattle, rodents and birds) with the same intensity
(Culicoides punctatus, C. vexans, Aedes excrucians, Ae. cinereus, Titanopteryx maculata).
Some species prefer definite hosts-providers: birds Culicoides odibilis, C. reconditus,
Culex pip.iens and Aedes caspius, rodents — Culicoides circumscriptus, C. obsoletus, Aedes
vexans, big animals — Culicoides nubeculosus, C. stigma, Anopheles maculipennis. In each biocenosis definite relations are composed between blood-sucking insects and providers. These relations are conditioned by many factors.